“Hanging: Facts and Reasons in Present Perspective” - Chowdhury, Md Habibuzzaman; Tanjilul Haque, Syed Mohammad (Anwer Khan Modern Medical College Journal, 2022)
Abstract not available AKMMC J 2021; 12(2): 68-69